Analyzing the Influence of Dividend Policy on Corporate Value: A Financial Perspective with Haier as a Case Study - Danni, Wang; Qi, Zhong (STIE Malangkucecwara, 2024)
The dividend policy plays a pivotal role in stabilizing stock prices and sustaining investor enthusiasm for listed companies. It not only significantly impacts the interests of management, investors, and creditors but also has long-term implications for the company's development. However, most studies on Chinese enterprises' dividend policies primarily rely on empirical research methods, with limited literature available on individual companies. The utilization of a case analysis methodology in this study has significantly enhanced the research cases related to China's dividend policies, thereby providing valuable insights for the advancement of analogous industries and the formulation of future dividend policies. In this study, Haier Smart Home Co., Ltd. (referred to as